Administrative competency and the effectiveness of school administration among teachers of Chia Chai School under the Office of the Private Education Commission Photharam District, Ratchaburi Province - Akkapatkosit, Manoch; Wiwatchankit, Sopee; Kumhom, Naitawan (RATANABUTH JOURNAL, 2022)
The purpose of this study was to study the level of 1) managerial competency 2) to study the effectiveness of school administration and 3) to study the relationship between administrative competency and the effectiveness of school administration of teachers at Chia Chai School. Under the Office of the Private Education Commission, Photharam District Ratchaburi. The population used in this research was 90 personnel. The tool used was a statistical questionnaire used to analyze the data. frequency distribution Finding the percentage mean standard deviation and analysis Pearson's Product Moment Correlation Coefficient. The results of the study found that most of the respondents were female, 70 people aged 30-40 years, 40 people, 88 people with bachelor's degree, average monthly income 10,000-20,000 baht, 80 people, work experience less than 5 years. 56 people 1) Executive competency Overall, it is at a high level. When considering each aspect, it was found that the first place was the aspect of lumbar self-development, followed by the aspect of achievement. and the final morality, ethics and professional ethics 2) Management effectiveness the overall picture is at a high level. Considering each aspect, it was found that the first place was the ability to solve problems within the school. followed by the ability to produce high-achieving students. The ability to change and develop schools and the final ranking is the ability to develop students to have a positive attitude; and 3) The relationship between administrative competency and the effectiveness of school administration of teachers. It was found that the pair with the highest correlation was executive competence There was a high level of positive correlation with effectiveness.